Evaluating the Thermal Performance of Shell-and-Tube Heat Exchangers: The Role of Flow Rate in Water-Based Systems - Afgani, Abduh Al; Zaidar, Chilfi; Saputra Sigalingging, Wanri; Sukarman; Khoirudin, Khoirudin; Abdulah, Amri (Jurnal Teknik Mesin Mechanical Xplore, 2024)
This research investigates the performance of water as a working fluid in the shell side of shell-and-tube heat exchangers (STHEs), explicitly analyzing how variations in flow rate influence the heat transfer coefficient, pressure drop, and friction factor characteristics. Experiments were conducted using an STHE with a SUS 201 stainless steel shell and a pure copper tube featuring an inner diameter of 10 mm and an outer diameter of 13 mm. The flow rates of the cold fluid varied at 9, 10, and 12 liters per minute (LPM), while the hot fluid flow was maintained at a constant rate of 6.67 LPM. A 600 W heater, regulated by a PID system, was utilized to evaluate thermal performance, with water serving as the hot fluid on the shell side and the cold fluid on the tube side. Results demonstrate a significant increase in both the heat transfer coefficient and the heat transfer rate with higher flow rates of the cold fluid, with the maximum heat transfer coefficient recorded at 12 LPM and the minimum at 9 LPM. The STHE exhibited high efficiency, with heat transfer rate differences between the shell and tube sides remaining below 5%. Although pressure fluctuations were observed with increasing flow rates, they did not substantially affect the friction factor, indicating a predominantly turbulent flow regime. These findings provide critical insights for optimizing heat transfer performance in STHEs, contributing to advancements in thermal management technologies and enhancing the design of efficient heat exchangers.